A Survey of Nanoindentation Studies on HPT‐Processed Materials. Issue 1 (20th August 2019) - Choi, In-Chul; Jang, Jae-il
Abstract : The development of high‐pressure torsion (HPT) processing has increased the possibility for achieving significant grain refinement, which leads to a material's ability to produce ultrafine‐grained or nanocrystalline materials having enhanced strength without a large expense of ductility at room temperature. Since the applied strain is locally changed across the sample disc during HPT, the microstructure and thus mechanical properties vary within the disc. Recently, as a promising tool for characterizing the mechanical behavior of the local regions within the disc, the nanoindentation technique becomes widely used mainly due to its simple and easy testing procedures and the requirement of only small volume of material. The nanoindentation technique provides important clues to better understand the relation between microstructural refinement and mechanical property enhancement of the HPT‐processed materials. Here, the nanoindentation studies performed on various HPT‐processed materials are reviewed with focus on a variety of micromechanical properties that can be estimated by nanoindentation and the interesting results are reported in the available literature. Abstract : For better understanding of the relation between refined microstructure and mechanical behavior of high‐pressure torsion (HPT)‐processed materials, the nanoindentation technique has been widely used under various conditions. Here, the nanoindentation studies performed on various HPT‐processed materials are reviewed with focus on a variety of micromechanical properties that can be estimated by nanoindentation and the interesting results in the literature.